2007
DOI: 10.1111/j.1440-1819.2007.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic classification and demographic features in 283 patients with somatoform disorder

Abstract: A total of 283 patients with somatoform disorder (SFD) seen in a psychiatry clinic were surveyed and their diagnostic subtypes, demographic features, and comorbidities, analyzed. The results indicate that: (i) SFD comprises 5.8% of first-visit outpatients; (ii) undifferentiated SFD (USFD) and SFD not otherwise specified (SFD-NOS) account for the majority of patients; (iii) there are 1.7-fold more women than men; (iv) age of onset is lower in patients with somatization disorder or body dysmorphic disorder and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Compared with other somatoform disorder groups, our body‐dysmorphic‐disorder patients were younger, were mostly single, and had more co‐morbidity. Our results are in line with the literature (Grover et al, ; Kuwabara et al, ; Leikness et al, ; Steinbrecher & Hiller, ). Most of our patients had co‐morbid disorders, especially the combination of anxiety and mood disorders, which is also in line with other studies (Carlier et al, ; Grover et al, ; Hanel et al, ; Jank, Liegl, Böckle, Vockner, & Pieh, ; Lieb et al, ; Löwe et al, ; Means‐Christensen, Roy‐Byrne, Sherbourne, Craske, & Stein, ; de Waal et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Compared with other somatoform disorder groups, our body‐dysmorphic‐disorder patients were younger, were mostly single, and had more co‐morbidity. Our results are in line with the literature (Grover et al, ; Kuwabara et al, ; Leikness et al, ; Steinbrecher & Hiller, ). Most of our patients had co‐morbid disorders, especially the combination of anxiety and mood disorders, which is also in line with other studies (Carlier et al, ; Grover et al, ; Hanel et al, ; Jank, Liegl, Böckle, Vockner, & Pieh, ; Lieb et al, ; Löwe et al, ; Means‐Christensen, Roy‐Byrne, Sherbourne, Craske, & Stein, ; de Waal et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Compared with other somatoform disorder groups, our body-dysmorphic-disorder patients were younger, were mostly single, and had more co-morbidity. Our results are in line with the literature (Grover et al, 2015;Kuwabara et al, 2007;Leikness et al, 2008;. Most of our patients had co-morbid disorders, especially the combination of anxiety and mood disorders, which is also in line with other studies (Carlier et al, 2014;Grover et al, 2015;Hanel et al, 2009;Jank, Liegl, Böckle, Vockner, & Pieh, 2017;Lieb et al, 2002;Löwe et al, 2008 Carlier et al, 2014;Maier & Falkai, 1999;de Reus, van den Berg, & Emmelkamp, 2013 Our results further showed that few variables could predict treatment course of somatoform disorders: the PSC total score, body dysmorphic disorder, and hypochondriasis were significant predictors for the course of the symptoms, whereas the PSC total score was the only significant predictor for the course of functioning.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, undifferentiated somatoform disorders do not constitute a homogenous group, but present high comorbidity with other psychiatric disorders. Among these disorders, anxiety and major depression are most common and are known to affect cognitive performance 11,23,41,42 …”
Section: Discussionmentioning
confidence: 99%
“…reported that approximately 8.6% of those seeking consultation had various forms of somatoform disorders 22 . Despite the well‐accepted view that certain cultural patterning may reinforce the tendency to somatize in non‐Western cultures, 5,6,23,24 no study to our knowledge has yet established whether individuals who somatize are marked with cognitive impairment. This current type of study has the potential to shed light on the cognitive impairment suffered in such a debilitating condition, which is often impervious to available treatment.…”
mentioning
confidence: 99%
“…It's a highly prevalent disorder in the general population, especially in primary practices, and causes social, economic, and psychological impacts [1][2][3][4][5][6][7][8] . Despite persistent somatoform pain disorder is a chronic and disabling condition, there is a paucity of work on its etiology and treatment.…”
Section: Introductionmentioning
confidence: 99%